Bioanalysis in special populations. (December 2014) - Unknown
As part of this special focus issue, Bioanalysis invited a selection of leading researchers to express their views on bioanalysis in special populations. The topics covered include a discussion of specific population-related factors that can affect sample analysis, technological advances and challenges relating to matrix effects. Their responses provide a valuable insight into current considerations, as well as future developments in the field.